Unsteady ground: understanding the problem of BPPV in the world of sports - Nowak, Wojciech; Sawicki, Mirosław; Mikołajczyk, Jagoda; Krzemińska, Paulina; Gołębski, Maciej; Kukla, Zuzanna; Musialik, Sebastian; Mieruszyńska, Stella; Włosiański, Jakub; Sadowska, Izabela (Quality in Sport, 2025)
Introduction: Dizzyness and Vertigo are one of the most common symptoms presented by patients, often the symptoms are caused by BPPV. BPPV may by provoked by certain types of impacts, head motion and other various factors including sport practice. In modern world, sport has become a part of everyday life, both in professional in amateur matter. Different sports, may lead to different types of injuries and related complications, one of them is dizzyness and vertigo. We investigated the existing data about the prevalence of BPPV related to certain types of physical activity. Different sports vary in the movement profile, amount and frequency of impacts. Furthermore, the injuries resulting from physical activity are not always associated with direct hits. Presenting all at once: the data, diagnostic and treatement strategy, we resume the existing knowledge on the phenomenon of BPPV in physical activity. Purpose of work: The article was completed to analyze the available data on the prevalence of BPPV in sports practitioners. This aims to facilitate the prompt resolution of vertigo symptoms in affected individuals and to identify potential, less obvious risk factors that may predispose athletes to this condition. State of Knowledge: Even though the knowledge about the etiology and risk factors of BPPV has significantly advanced in the last decade, more than half of all cases is are still classified as idiopathic. While data on possible new risk factors is growing, it often consists of case reports or orginal studies with small sample sizes, limiting its generalizability. It is widely believed though that certain types of movement may play a role in triggering BPPV. Material and methods: This article is based on a comprehensive review of the literature, conducted using PubMed and Google Scholar. The research focused on studies concerning the prevalence, etiology and risk factors of BPPV, particularly in sports practitioners.